Molecular-level architectural design using benzothiadiazole-based polymers for photovoltaic applications - Viswanathan, Vinila N.; Rao, Arun D.; Pandey, Upendra K.; Kesavan, Arul Varman; Ramamurthy, Praveen C. (Beilstein Journal of Organic Chemistry, 2017)
A series of low band gap, planar conjugated polymers, P1 (PFDTBT), P2 (PFDTDFBT) and P3 (PFDTTBT), based on fluorene and benzothiadiazole, was synthesized. The effect of fluorine substitution and fused aromatic spacers on the optoelectronic and photovoltaic performance was studied. The polymer, derived from dithienylated benzothiodiazole and fluorene, P1, exhibited a highest occupied molecular orbital (HOMO) energy level at −5.48 eV. Density functional theory (DFT) studies as well as experimental measurements suggested that upon substitution of the acceptor with fluorine, both the HOMO and lowest unoccupied molecular orbital (LUMO) energy levels of the resulting polymer, P2, were lowered, leading to a higher open circuit voltage and short circuit current with an overall improvement of more than 110% for the photovoltaic devices. Moreover, a decrease in the torsion angle between the units was also observed for the fluorinated polymer P2 due to the enhanced electrostatic interaction between the fluorine substituents and sulfur atoms, leading to a high hole mobility. The use of a fused π-bridge in polymer P3 for the enhancement of the planarity as compared to the P1 backbone was also studied. This enhanced planarity led to the highest observed mobility among the reported three polymers as well as to an improvement in the device efficiency by more than 40% for P3.
Keywords: bulk heterojunction; donor–acceptor–donor polymer; low band gap polymer; organic photovoltaics

(untitled) - Dennler, G.; Scharber, M. C.; Brabec, C. J. (Adv. Mater., 2009)

(untitled) - Sariciftci, N. S.; Smilowitz, L.; Heeger, A. J.; Wudl, F. (Science, 1992)

(untitled) - Kraabel, B.; Hummelen, J. C.; Vacar, D.; Moses, D.; Sariciftci, N. S.; Heeger, A. J.; Wudl, F. (J. Chem. Phys., 1996)

(untitled) - Brabec, C. J.; Zerza, G.; Cerullo, G.; De Silvestri, S.; Luzzati, S.; Hummelen, J. C.; Sariciftci, S. (Chem. Phys. Lett., 2001)

(untitled) - Zhao, J.; Li, Y.; Yang, G.; Jiang, K.; Lin, H.; Ade, H.; Ma, W.; Yan, H. (Nat. Energy, 2016)

(untitled) - Chen, C.-C.; Chang, W.-H.; Yoshimura, K.; Ohya, K.; You, J.; Gao, J.; Hong, Z.; Yang, Y. (Adv. Mater., 2014)

(untitled) - Hu, H.; Jiang, K.; Yang, G.; Liu, J.; Li, Z.; Lin, H.; Liu, Y.; Zhao, J.; Zhang, J.; Huang, F.; Qu, Y.; Ma, W.; et al. (J. Am. Chem. Soc., 2015)

(untitled) - Cheng, Y.-J.; Yang, S.-H.; Hsu, C.-S. (Chem. Rev., 2009)

(untitled) - Bessette, A.; Hanan, G. S. (Chem. Soc. Rev., 2014)

(untitled) - Zhan, X.; Zhu, D. (Polym. Chem., 2010)

(untitled) - Cheng, Y.-J.; Yang, S.-H.; Hsu, C.-S. (Chem. Rev., 2009)

(untitled) - Deng, P.; Zhang, Q. (Polym. Chem., 2014)

(untitled) - Zhou, H.; Yang, L.; You, W. (Macromolecules, 2012)

(untitled) - Bundgaard, E.; Krebs, F. C. (Sol. Energy Mater. Sol. Cells, 2007)

(untitled) - Brédas, J.-L.; Norton, J. E.; Cornil, J.; Coropceanu, V. (Acc. Chem. Res., 2009)

(untitled) - Huang, Y.; Kramer, E. J.; Heeger, A. J.; Bazan, G. C. (Chem. Rev., 2014)

(untitled) - Chochos, C. L.; Choulis, S. A. (Prog. Polym. Sci., 2011)

(untitled) - Murali, M. G.; Rao, A. D.; Ramamurthy, P. C. (RSC Adv., 2014)

(untitled) - Kottokkaran, R.; Rao, A. D.; Ramamurthy, P. C. (MRS Online Proc. Libr., 2013)

(untitled) - Hoogmartens, I.; Adriaensens, P.; Vanderzande, D.; Gelan, J.; Quattrocchi, C.; Lazzaroni, R.; Bredas, J. L. (Macromolecules, 1992)

(untitled) - Kitamura, C.; Tanaka, S.; Yamashita, Y. (Chem. Mater., 1996)

(untitled) - Yamamoto, T.; Zhou, Z.-h.; Kanbara, T.; Shimura, M.; Kizu, K.; Maruyama, T.; Nakamura, Y.; Fukuda, T.; Lee, B.-L.; Ooba, N.; Tomaru, S.; Kurihara, T.; et al. (J. Am. Chem. Soc., 1996)

(untitled) - Sotzing, G. A.; Reynolds, J. R.; Steel, P. J. (Adv. Mater., 1997)

(untitled) - Zhang, Q. T.; Tour, J. M. (J. Am. Chem. Soc., 1998)

(untitled) - Lu, Y.; Xiao, Z.; Yuan, Y.; Wu, H.; An, Z.; Hou, Y.; Gao, C.; Huang, J. (J. Mater. Chem. C, 2013)

(untitled) - Dang, D.; Chen, W.; Yang, R.; Zhu, W.; Mammo, W.; Wang, E. (Chem. Commun., 2013)

(untitled) - Kularatne, R. S.; Taenzler, F. J.; Magurudeniya, H. D.; Du, J.; Murphy, J. W.; Sheina, E. E.; Gnade, B. E.; Biewer, M. C.; Stefan, M. C. (J. Mater. Chem. A, 2013)

(untitled) - Fei, Z.; Boufflet, P.; Wood, S.; Wade, J.; Moriarty, J.; Gann, E.; Ratcliff, E. L.; McNeill, C. R.; Sirringhaus, H.; Kim, J.-S.; Heeney, M. (J. Am. Chem. Soc., 2015)

(untitled) - Gohier, F.; Frère, P.; Roncali, J. (J. Org. Chem., 2013)

(untitled) - Roncali, J. (Acc. Chem. Res., 2009)

(untitled) - Zhu, Z.; Waller, D.; Gaudiana, R.; Morana, M.; Mühlbacher, D.; Scharber, M.; Brabec, C. (Macromolecules, 2007)

(untitled) - Li, Y.; Chang, C.-Y.; Chen, Y.; Song, Y.; Li, C.-Z.; Yip, H.-L.; Jen, A. K.-Y.; Li, C. (J. Mater. Chem. C, 2013)

(untitled) - Xu, Y.-X.; Chueh, C.-C.; Yip, H.-L.; Ding, F.-Z.; Li, Y.-X.; Li, C.-Z.; Li, X.; Chen, W.-C.; Jen, A. K.-Y. (Adv. Mater., 2012)

(untitled) - Son, H. J.; Lu, L.; Chen, W.; Xu, T.; Zheng, T.; Carsten, B.; Strzalka, J.; Darling, S. B.; Chen, L. X.; Yu, L. (Adv. Mater., 2013)

(untitled) - Chen, J.; Cao, Y. (Acc. Chem. Res., 2009)

(untitled) - Ying, L.; Zou, J.; Yang, W.; Zhang, A.; Wu, Z.; Zhao, W.; Cao, Y. (Dyes Pigm., 2009)

Gaussian 09, Revision C.01 (Gaussian, Inc., 2010)

(untitled) - McCormick, T. M.; Bridges, C. R.; Carrera, E. I.; DiCarmine, P. M.; Gibson, G. L.; Hollinger, J.; Kozycz, L. M.; Seferos, D. S. (Macromolecules, 2013)

(untitled) - Gedefaw, D.; Tessarolo, M.; Zhuang, W.; Kroon, R.; Wang, E.; Bolognesi, M.; Seri, M.; Muccini, M.; Andersson, M. R. (Polym. Chem., 2014)

(untitled) - Sun, J.; Zhu, Y.; Xu, X.; Lan, L.; Zhang, L.; Cai, P.; Chen, J.; Peng, J.; Cao, Y. (J. Phys. Chem. C, 2012)

(untitled) - De Leeuw, D. M.; Simenon, M. M. J.; Brown, A. R.; Einerhand, R. E. F. (Synth. Met., 1997)